Ballistic Impact Response of Al0.1CoCrFeNi High‐Entropy Alloy. Issue 6 (22nd June 2020) - Muskeri, Saideep; Choudhuri, Deep; Jannotti, Philip A.; Schuster, Brian E.; Lloyd, Jeffrey T.; Mishra, Rajiv S.; Mukherjee, Sundeep
Abstract : In this manuscript the ballistic impact response of a high entropy alloy is demonstrated along with detailed description of the corresponding deformation and fracture mechanisms. The high entropy alloy studied could be potentially transformative for next generation armor applications. Further details can be found in article, number 2000124, by Sundeep Mukherjee, Jeffrey T. Lloyd, and co‐workers